Throwing shoulder adaptations are not related to shoulder injury or pain: A preliminary report - Strama, E.; Keenan, K. A.; Sell, T.; Faherty, M.; Rafferty, D.; Salesi, K.; Varnell, M. (Sports Health: A Multidisciplinary Approach, 2024)
Background: Overhead throwing in baseball and softball athletes induces shoulder adaptations theorized to increase risk of shoulder musculoskeletal injury (MSI) and/or pain due to range of motion (ROM) deficits.